Analysis of Mathematical Connection Ability Through Project Asesmen Sumatif Akhir Jenjang (ASAJ) in Junior High School - Sabriena, Rinna; Kana Hidayati (Program Studi Tadris Matematika Universitas Islam Negeri (UIN) Salatiga, 2024)
This study aims to assess students' ability to link mathematical concepts with recycling projects through the implementation of an end-of-level summative assessment (ASAJ). The recycling project was chosen as the final assessment to enrich students' experience through direct application to real-world situations. This type of research is descriptive with a qualitative approach. The subjects in this study were four groups selected based on the criteria determined by the researcher. The data collection techniques used were documentation in the form of student reports and interviews with teachers and students. This assessment is the final assessment of project-based ninth grade students with the theme of 3R (reuse, reduce, recycle). The results showed that students can process used goods or waste that is difficult to decompose into goods that have selling value. In addition, the implementation of this assessment shows that students are not only able to identify and apply mathematical patterns and concepts in this project but also use mathematical calculations and data to make relevant decisions during the project process. This ability can be seen in how students connect mathematical theories with practical contexts such as scale calculations and social arithmetic. This research is expected to be an illustration for schools or teachers who want to implement project-based learning and assessment in addition to providing a more contextual and applicable learning experience, especially for the surrounding environment.